Artificial intelligence in language learning: a tool or a threat? - Gómez-Sigsig, Diana Andrea; Zambrano-Batallas, Ruben Dario; Gómez-Sigsig, Johnny Fernando (EPISTEME KOINONIA, 2026)
ABSTRACT The objective of this study was to analyze artificial intelligence in language learning, as either a tool or a threat. Methodologically, it was based on a descriptive quantitative study that utilized a survey method, using a structured Likert scale questionnaire. This instrument was validated by experts and had a Cronbach’s alpha coefficient of 0.80, indicating acceptable reliability. As a result, the development of the four skills was observed: speaking, through the creation of innovative oral activities; listening, through participation in listening comprehension exercises; reading, through the comprehension of various texts; and writing, through the production of written work. In conclusion, the use of artificial intelligence has been perceived as a tool when employed for academic progress and for life; conversely, it has constituted a threat when used merely to complete tasks without promoting meaningful learning.